Changing attitudes to mathematics in primary school teachers in England. Issue 2 (3rd April 2019) - McAteer, Mary; Grinyer, Victoria
ABSTRACT: Concern about attitudes to mathematics and mathematics education is not unique to England. Studies across the world, including the USA, Canada and Australia, indicate similar concerns. This research aimed to identify the factors that impacted on the formation of teachers' attitudes to mathematics in primary schools in England and to discover how these have been shaped and/or changed during an in-service professional development programme, The Mathematics Specialist Teacher Programme (MaST). We thus take a unique position in attempting to develop a possible model for reducing teacher mathematics anxiety, and its consequences in classrooms. Findings were analysed using key typologies of professional learning and and revealreveal that teachers who undertook the programme made strong, explicit links between previous experiences of being taught mathematics, their own feelings of mathematics confidence and competence, and levels of mathematics anxiety. High-level collaboration with colleagues and expert facilitators were evident as significant factors in overcoming this anxiety.